The Optimum Dose of Nitrogen, Phosporus, and Potassium to Improve Soybean (Glycine max (L) Merr) Productivity on Kayu Putih (Melaleuca cajuputi) Stands - Roni Ismoyo Jati; Tohari Tohari; Priyono Suryanto (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2017)
It was necessary to obtain optimum dose of nitrogen, phosphorus, and potassium obtained through fertilisation in order to improve productivity in the intercropping. Kayu putih tree was cultivated in Yogyakarta for oil production, and the inter-row was designed for intercropping plants, including soybean. The objective of present study was to obtain optimum dose of urea, SP-36, and KCl for soybean intercropped with kayu putih. The experiment was conducted in Menggoran Forest Resort (RPH Menggoran), Playen Forest Section (BDH Playen), Yogyakarta Forest Management District (KPH Yogyakarta) using split-split plot design. The main plot was urea, subplot was SP-36, and sub-subplot was KCl. Fertilisation consisted of three levels (0, 25, 50 kg ha-1 of urea), (0, 150, 300 kg ha-1 of SP-36) and (0, 75, 150 kg ha-1 of KCl). The results showed that application of 50 kg ha-1 urea, 300 kg. ha-1 SP-36, and 150 kg. ha-1 KCl increased N, P, K uptake per hectare as much as 16.23 kg N ha-1, 86.27 kg P ha-1, 40.02 kg K ha-1, respectively. There was positive interaction between urea and SP-36, SP-36 and KCl at leaf area, photosynthetic rate, number of seeds per plants, seed weight per plants, and seed weight per hectare. Under kayu putih intercropping, optimum dosage of urea, SP-36 and KCl were 0, 298.03 and 87.12 kg ha-1, respectively. These combination enabled to produce maximum seed weight of 2.01 tons. ha-1.